(untitled) (Estudios Sociales, 2020)
CITIZENS OF THE 21ST CENTURY, ON EXISTENTIAL CITIZENSHIP IN LATIN AMERICA This paper starts from the budget that citizenship is a set of rights that act in a unified way, so that when one of its spheres is affected, this implies consequences for the whole. During the twentieth century, civil, social and political spheres predominated, while in the 21st century, existential citizenships emerge, based on recognition, quality of life and dignity. After stating the characteristics of this type of citizenship, the situation in Latin American countries is reviewed.